Parametric study in shear buckling capacity of sinusoidal corrugated steel web - Wong, Sui Kieng; Abu Bakar, Nabilah; Safiee, Nor Azizi; Mohd. Nasir, Noor Azline (Universiti Teknologi Malaysia, 2022)
Sinusoidal corrugated steel web has gradually gained attention over trapezoidal corrugated steel web. The design of shear buckling capacity for the trapezoidal corrugated web is governed by interactive buckling which normally has the lowest value among global, local and interactive failures. It was discovered in some studies that the shear buckling in a sinusoidal section is found to be governed by either local or global failures, where there is a lack of study in this area. The purpose of this study is to determine the effect of web thickness, web height, and sinusoidal radius on the shear buckling capacity and buckling mode in the sinusoidal corrugated steel web. Finite element analysis was conducted on 150 specimens with different radius of sinusoidal corrugated web, web height and web thickness to investigate their influence to the shear buckling capacity of the sections. The result shows that the increase in web thickness has been shown to increase the shear buckling capacity linearly. The increase in web height and radius of corrugated web reduce the shear buckling capacity of the beam exponentially. The results from finite element analysis are compared with an analytical equation from existing literature. It is found that the equation gives a conservative prediction of the shear capacity, however, could be used for a radius greater than 150 mm